Epidemiological Clinical Features and Evolution of Gastroduodenal Ulcer Bleeding in a Tertiary Care Hospital in Spain, during the Last Seven Years. (8th December 2013) - Lauret, Eugenia; Herrero, Jesús; Blanco, Lorena; Castaño, Olegario; Rodriguez, Maria; Pérez, Isabel; Alvarez, Verónica; Suárez, Adolfo; Rodrigo, Luis
Abstract : Background . Gastroduodenal ulcer bleeding is a common medical emergency. The aim of this study was to analyze the characteristics of bleeding episodes and to identify changes in the clinical trends over seven years. Methods . Retrospective observational clinical study on a cohort of 272 consecutive adult patients with peptic ulcer bleeding, during the 2006–2012 period. Results . Mean annual admission rate was 12.8 per 100.000 inhabitants. Men were predominant (71%), with a mean age of 66.6 years. Comorbidities were present in 131 cases (48.2%) and 156 patients (57.4%) had received ulcerogenic drugs. Duodenal ulcer was the commonest location (61%). Endoscopic therapy was necessary in 183 cases (67.3%) and rebleeding occurred in 30 patients (11%). Overall mortality rate was 5.5%, with a significant association with the presence of comorbidities (P < 0.01 ). There were no differences in trends of annual hospitalization, clinical features at presentation, and outcomes during this 7-years period. Conclusions . Annual hospitalization rates and prognosis of peptic ulcer bleeding have remained unchanged in the study period. This may be due to the fact that the effect of improved approach on this condition is probably counteracted by risk factors such as older age, severe comorbidities, and ulcerogenic drugs consumption, which have also remained stable over recent years.